Monte Carlo simulation of direction sensitive antineutrino detection - Blanckenberg, J. P (Jacobus Petrus) (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Physics))--University of Stellenbosch, 2010.